Pengembangan Budidaya Sayur Organik di Pesantren Nurul Islam Jember dengan Teknologi Komposting Takakura dan Sistem Tanam Vertikultur - Dwi Erwin Kusbianto; Sholeh Avivi; Bakhroini Habriantono; Riza Yuli Rusdiana; Mohammad Nur Khozin (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
Nurul Islam Islamic boarding school Jember is one of the modern Islamic boarding schools that teaches religion, science, and technology. Organic vegetable cultivation training using Takakura technology and a verticulture planting system aims to increase the knowledge awareness, and skills of the students. Besides, this activity has a positive impact on health, waste management, environmental harmony, vegetable crop production, land effectiveness and adds economic value. Takakura technology produces odorless and nutritious compost products. Takakura compost is used as a growing medium in verticulture pipes. The skills of cultivating organic vegetables using Takakura technology and a verticulture planting system are very useful for the students. Technically, the implementation of this program includes material presentation, leaflet giving, and hands-on practice. Cultivation that is carried out includes making media, preparing seeds, preparing planting media, transplanting seeds into verticulture media, and plant care. The result of training activity can improve the knowledge and competence of student to produce organic fertilizer and vegetable through the technology that transfer for them.